KETENTUAN-KETENTUAN PENGGABUNGAN DUA NIAT ATAU LEBIH DALAM SATU IBADAH - Arif Husnul Khuluq; Fathan Jihadul Islam; Winning Son Ashari (Al-Majaalis : Jurnal Dirasat Islamiyah, 2023)
Intention is one of the determinants of the acceptance of a servant's worship. Without the right intention, one's worship becomes empty even though the rituals he performs are full of hardships. Among the problems of fiqh in the chapter of intentions is the merging of two intentions in one worship. This study aims to explain the provisions explained by the scholars to be able to combine intentions in one worship only. This study uses a descriptive qualitative method by looking at the relevant literature data. The results showed that not all worship with the same ritual can be combined in its intentions. But there is a stipulation that worship that can be combined is only between worship that is meant by its essence and that which is not meant by its essence. While worship that is both meant by its essence, it should not be combined and must be carried out one by one. So a Muslim should pay attention to the evidences of the worship that he will combine his intentions and seek the truth by seeking explanations from the scholars so that this combination is valid, so that his worship can be accepted and does not become a useless practice because it is rejected.